Effect of vacuum and ethanol pretreatment on infrared-hot air drying of scallion (Allium fistulosum). (15th October 2019) - Wang, Xule; Feng, Yabin; Zhou, Cunshan; Sun, Yanhui; Wu, Bengang; Yagoub, Abu ElGasim A.; Aboagarib, Elmuez Alsir A.
Highlights: A new drying method for scallion was proposed: Ethanol + VC and IR + AD. Ethanol + VC significantly enhanced the drying rate compared to Control, Ethanol and Water + VC. The quality of dehydrated scallions was improved by Ethanol + VC. The Vacuum pretreatment effectively avoid shrinkage caused by drying of scallions. The pre-treatment by Ethanol + VC eliminates process of sterilizing scallions before drying. Abstract: This study examined the effects of vacuum, ethanol pretreatment, and infrared-hot air drying methods on the characteristics and quality of scallion slices. The pretreatment of scallion includes four conditions: 1) Control: soaking in distilled water under normal pressure, 2) Ethanol: soaking in 75% ethanol under normal pressure, 3) Water + VC: soaking in distilled water under a vacuum of 0.6 bar, 4) Ethanol + VC: soaking in 75% ethanol under a vacuum of 0.6 bar. The pretreatment times were 5, 10, 20 and 30 min. The drying process was done in an infrared hot air drying oven at 60 °C. The ethanol pretreated samples exhibited better rehydration, odor, vitamin C retention, bactericidal effect and significantly reduced drying time. Water + VC samples showed better scallion morphology and color. Ethanol + VC samples showed the combined advantages of ethanol and Water + VC pretreatments. Therefore, Ethanol + VC pretreatment can significantly improve the drying rate and quality of scallion.